Solidarity and A.I. for Transitioning to Crowd Work during COVID-19 - Savage, Saiph; Jarrahi, Mohammad (2020)
ABSTRACT Due to the COVID-19 pandemic, a number of gig workers who engaged in location-based gig work (e.g., Taskrabbit, Care.com, or Wag) have had to transition to new jobs that are independent of location (e.g., online freelancing or crowd work). However, this has been a difficult transition. Especially because in this new environment, gig workers now have to compete globally for work, and they also have to focus on work interactions that are primarily online (instead of gig work that takes place within specific physical locations or within in-person meetings). In this paper, we build on our extensive research on gig work, gig literacy and the design of crowdsourcing systems, to present an intelligent architecture for helping workers transition to new gig jobs in times of global crisis. Our intelligent architecture uses machine learning and draws on collective action theory to introduce “Solidarity Brokers.” Our Solidarity Brokers are computational mechanisms that identify the best ways to build solidarity between workers with the purpose of mobilizing workers to help each other transition to new jobs. We finish by presenting a brief research agenda for intelligent tools that facilitate work transitions during the global pandemic and beyond. ABOUT THE AUTHOR/S Saiph Savage Microsoft Bing, Universidad Nacional Autonoma de Mexico saiph@uw.edu Saiph Savage is a researcher & engineer at Microsoft Bing and co-director of the Civic Innovation Lab at UNAM. She was named one of the 35 Innovators under 35 by the MIT Technology Review, won a 2.5 million dollar NSF grant to study systems to help displaced rural workers access better jobs and fight disinformation in their rural towns. Saiph has opened the area of HCI in rural West Virginia, and has lead governments in LATAM to adopt Human Centered Design to deliver better services to citizens. Mohammad Jarrahi University of North Carolina at Chapel Hill jarrahi@unc.edu Mohammad Jarrahi is an Associate Professor at the University of North Carolina at Chapel Hill. His research focuses on the use and consequences of information and communication technologies (ICTs) in extra-organizational contexts, and flexible work arrangements (e.g., mobile and gig work). He is also interested in the role of artificial intelligence (AI) in the future of work. New Future of Work 2020, August 3–5, 2020 © 2020 Copyright held by the owner/author(s).